Change in Knowledge, Attitude and Practice Regarding Anae-mia among High School Girls in Rural Bangalore: An Health Educational Interventional Study - Tarikere, Pradeep S; Prakash B; Kulkarni, Praveen; Murthy, Narayana (National Journal of Community Medicine, 2018)
Background: Adolescent girls are particularly vulnerable to anemia compared.KAP assessment is suitable to evaluate the effectiveness of intervention programs. This study was carried out to assess the knowledge, attitude and practice regarding anemia and improvement in same after health education among high school girls in rural Bangalore. Materials and Methods: It’s a cross sectional interventional study. All girls were included age group 14 to 16 years and those who did not consent were excluded from the study which was carried out in Govt High School in Hoskote, Rural Bangalore for a period of three months. All the data were entered in Microsoft excel and analyzed using SPSS v 22. Results: Among 100 study participants, 78 % belonged to age group of 13-14 years, 85% belonged to nuclear family. Initial assessment showed Knowledge being poor, Attitude being negative and practice being unsatisfactory and health education were given through various forms. Conclusion: The overall findings of the study showed the knowledge, attitude and practices of female adolescents are moving in a desirable direction post health education. Comprehensive nutritional education regarding anemia and consequences among adolescents can yield a great dividend in future life of women.